TUS MART Web Commerce Design As A Digital Marketing Effort For Urban Farming Products Using Kansei Engineering - Zunaidi, Rizqa Amelia; Hamidah, Dwi Nur Azizah; Putra, Perdana Suteja; Hidayati, Sri; Chandra, Huki; Mardhiana, Hawwin; Wulandari, Eka Devi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2024)
This study focused on agricultural products, utilizing the Kansei Engineering methodology to enhance user experience and align with digital marketing strategies. Kansei Engineering is applied to transform users' emotional needs into concrete design elements, creating a website interface that meets both functional and emotional requirements. By emphasizing attributes like engagement, transparency, interactivity, and ease of use, the website aims to provide a personalized, intuitive, and satisfying experience, fostering user connection and loyalty. The results demonstrate that Kansei Engineering significantly enhances emotional satisfaction and functional effectiveness, positively impacting customer engagement and retention—key elements in digital marketing. In this study, the